Improvement of energy consumption in MIMO with cognitive radio networks - Zinah Osamah Dawood; Heba M. Fadhil (Institute of Advanced Engineering and Science, 2022)
The employment of cognitive radio (CR) is critical to the successful development of wireless communications. In this field, especially when using the multiple input multiple output (MIMO) antenna technology, energy consumption is critical. If the principal user (PU) is present, developers can utilize the energy detecting approach to tell. The researchers employed two distinct phases to conduct their research: the intense and accurate sensing stages. After the furious sensing step was completed, the PU user was identified as having a maximum or minimal energy channel. There are two situations in which the proposed algorithm's performance is tested: channels for fading AWGN and Rayleigh. When the proposed methods' simulation results are compared with conventional approaches, the complexity of MIMO was reduced by roughly 42% at low SNR levels. With 70 samples and an acceptable drop in detection performance, the results were suitable for further testing.